Water Quality Parameters and Macroinvertebrates Index of Biotic Integrity of the Jimma Wetlands, Southwestern Ethiopia - Yimer, Hayal Desta; Mengistou, Seyoum (Journal of Wetlands Ecology, 2010)
The wetlands located at the periphery of Jimma town, southwestern Ethiopia, have critical roles in providing a range of ecological and socio-economic benefits, yet they are subject to increasing anthropogenic disturbances, notably through agriculture, settlement, intensive grazing and brick-making. This study assessed the ecological status of these wetlands, and examined the scale of the human disturbances that local communities might impose on them. Macroinvertebrate communities, water quality parameters, and human disturbance scores were assessed. Except for electrical conductivity and water temperature, no significant difference (P < 0.05) was found in physico-chemical parameters between the sampled sites. Nitrate was the only parameter that correlated with significant influence on species richness of the sampled macroinvertebrates. A total of 10 metrics were used to generate the index of biotic integrity (IBI). This IBI was then tested based on macroinvertebrate data collected. Ways of assessing and evaluating the existing ecological status of the wetlands are discussed in the context of physico-chemical parameters, IBI based on macroinvertebrates and human disturbance scales. Key Words: Catchments land use; Water quality; Macroinvertebrate; Index of Biotic Integrity; Wetland DOI: 10.3126/jowe.v3i0.2265 Journal of Wetlands Ecology, (2009) Vol. 3, pp 77-93